Volume 6: Turbomachinery, Parts A, B, and C 2008
DOI: 10.1115/gt2008-50211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wakes and Secondary Flow on Re-Attachment of Turbine Exit Annular Diffuser Flow

Abstract: In this paper numerical results of wake and secondary flow interaction in diffuser flow fields are discussed. The wake and secondary flow are generated by a rotating wheel equipped with 30 cylindrical spokes with a diameter of 10 mm as a first approach to the turbine exit flow environment. The apex angle of the diffuser is chosen such that the flow is strongly separated according to the well-known performance charts of Sovran and Klomp [1]. This configuration has been tested in an experimental test rig at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Viewed in an historical context, the SAS model is an improvement of the Detached-Eddy Simulation (DES) approach by [14], with lower sensitivity to grid resolution. Ergorov and Menter [10] validated the SAS modification of the SST turbulence model for a series of applications Kluß et al [6] showed the advantages of the SAS-SST model concerning the flow separation prediction of a highly loaded diffuser downstream of a single stage rotor.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Viewed in an historical context, the SAS model is an improvement of the Detached-Eddy Simulation (DES) approach by [14], with lower sensitivity to grid resolution. Ergorov and Menter [10] validated the SAS modification of the SST turbulence model for a series of applications Kluß et al [6] showed the advantages of the SAS-SST model concerning the flow separation prediction of a highly loaded diffuser downstream of a single stage rotor.…”
Section: Methodsmentioning
confidence: 99%
“…the Reynolds shear stresses of the SAS simulation (6) are the sum of the resolved stresses by the SAS term and the modeled turbulence (k-term). The resolved stresses include solely statistical variations, whereas the stresses derived from the Bousinesqhypothesis includes both deterministic and stochastic stresses (as long as they are not resolved by the SAS approach).…”
Section: Normbaxialbvelocitymentioning
confidence: 99%
See 1 more Smart Citation